Animals in art and hybridization as basis for creative explorations (REVISTA NODO, 2011)
The article presents an outlook of the symbolic connotation given to the animal image throughout the history of art, from prehistoric times up to today, focusing on contemporary tendencies. It tackles the issue by analyzing the concept of conflictive beauty and its relation with abjection, horror and repulsion notions, and by studying animal roles as metaphors in art works and performances, their usage in pigments’ production, and the excesses towards animals committed by some artists in their proposals. Given its research/ creation approach, it examines the relation between human beings and one of the oldest parasites (the Ctenocephalides canis flea), and from that standpoint it suggests phobias and hybridization as foundation for graphic and creative explorations. It concludes that art, particularly since the early avant gardes of the twentieth century, has endowed its works with a language in which the meaning of “animalness” is portrayed through aesthetic categories that have gone beyond the beautiful to embrace the monstrous, the sinister and the ugly.
Keywords: Aesthetic categories; phobias; repulsion; horror